The Effect of Application of SAK-ETAP, Internal Control System, and Capacity of Cooperatives on the Development of Business in Cooperatives in Banda Aceh City - Fadhil Robih Zakwan Hasibuan; Indayani Indayani (Universitas Syiah Kuala, 2019)
Objective – This study aims to determine the effect of the application of SAK-ETAP, internal control systems, and cooperative management capacity on business development in cooperatives in Banda Aceh.Design/methodology – This study uses hypothesis testing. The sample of this study was selected using purposive sampling. The total number of observations obtained was 102 cooperatives in accordance with the sample criteria with 473 observational data. The type of data used was secondary data with data collection techniques through questionnaires. The data analysis technique used is the validity test, the reliability test, the classic assumption test, the multiple regression analysis tests.Results – The test results show that the adoption of SAK-ETAP affects business development in cooperatives, internal control systems affect business development in cooperatives, cooperative management capacity influences business development in cooperatives.